The Impact of Emotional Intelligence on Job performance in the Gulf Region - Shdaifat, Fayez Hamed Al; Zyoud, Adel Ali Yassin Al (International Journal of Emerging Trends in Social Sciences, 2021)
The aim of this research is to discover the impact of Emotional Intelligence (EI) on job performance among the employees in the gulf region. The results of recent researches indicate that EI is related positively with vital work manners. However, studies on EI have largely been conducted in the business field and in western countries. Therefore, there is a scarcity on EI studies in the context of public setting in the Gulf region, particularly in the medical field. A sample of 120 employees (doctors) was selected for this study, from which data was obtained. Regression analysis was applied as a statistical test to analyze the data. The findings revealed a significant relationship between emotional intelligence and job performance among doctors. This indicates that the increase of emotional intelligence will increase job’s performance. As previously mentioned, this study can help the managements and academics better understand the relationship among the variables. It can also help professionals in organization enhanced understand the relationship amongst these factors.